A Sandwich‐Like Hierarchically Porous Carbon/Graphene Composite as a High‐Performance Anode Material for Sodium‐Ion Batteries. Issue 8 (27th January 2014) - Yan, Yang; Yin, Ya‐Xia; Guo, Yu‐Guo; Wan, Li‐Jun
<x xml:space="preserve">Abstract</x> A sandwich‐like hierarchically porous carbon/graphene (G@HPC) composite is synthesized using a facile ionothermal process. The composite exhibits high specific capacity, remarkable cycling stability, and high‐rate capability because of the synergistic effect of low‐graphitized porous carbon with hierarchical structure and highly conductive graphene sandwiched between porous carbons. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>